2007
DOI: 10.1002/er.1259
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen utilization as a fuel: hydrogen-blending effects in flame structure and NO emission behaviour of CH4–air flame

Abstract: SUMMARYHydrogen-blending effects in flame structure and NO emission behaviour are numerically studied with detailed chemistry in methane-air counterflow diffusion flames. The composition of fuel is systematically changed from pure methane to the blending fuel of methane-hydrogen through H 2 molar addition up to 30%. Flame structure, which can be described representatively as a fuel consumption layer and a H 2 -CO consumption layer, is shown to be changed considerably in hydrogen-blending methane flames, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…In the UK, domestic gas usage contributes to 9% of nationwide CO 2 emissions (2007)(2008)(2009) [37,104]. In an attempt to lower CO 2 and NO x emissions, the addition of hydrogen fuel can be an effective solution [106,107].…”
Section: Direct Combustion Of Hydrogenmentioning
confidence: 99%
“…In the UK, domestic gas usage contributes to 9% of nationwide CO 2 emissions (2007)(2008)(2009) [37,104]. In an attempt to lower CO 2 and NO x emissions, the addition of hydrogen fuel can be an effective solution [106,107].…”
Section: Direct Combustion Of Hydrogenmentioning
confidence: 99%
“…However, the degradation problem in the PF algorithm significantly affects estimation accuracy. To solve this problem and improve the estimation accuracy, we adopt the genetic algorithm in the resampling of PF [37][38][39], which is called the genetic resampling particle filter (GPF). Previous works showed that the GPF performs better than the PF.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen blending effects on flame structure and NO emission behavior have been numerically investigated by Park et al [11] using detailed chemistry in methane-air counterflow diffusion flames. A computational study to investigate the effects of hydrogen addition on methane-air flames at different conditions has been performed in the study of Chen [12].…”
Section: Introductionmentioning
confidence: 99%